The Effectiveness of Da'wah Through Social-Media in Fostering the Interest of Da'wah Students of Islamic Communication and Broadcasting at North Sumatra State Islamic University - Fachrial Akbar; Mailin Mailin; Hasnun Jauhari Ritonga (International Journal of Science and Society, 2023)
This study aims to analyze the effectiveness of da'wah through social media in fostering interest in da'wah of Islamic communication and broadcasting students at North Sumatra State University. This research is categorized as quantitative research with associative methods and uses questionnaires as research instruments. The population in this study were Islamic Communication and Broadcasting Students of the State Islamic University of North Sumatra semester 3. The sampling technique used a non-probability sampling method, namely purposive sampling with a sample size of 109 students. The method used for hypothesis testing in this study is multiple linear regression method. Based on the research that has been done, it is found that the elements of da'wah effectiveness, namely interesting content through audio visual, content based on Koranic postulates, and content based on historical simultaneously have a positive and significant effect on da'wah interest. Social media elements, namely user content, application networking sites, and virtual social world simultaneously have a positive and significant effect on interest in da'wah. And interest in da'wah with elements of attention to da'wah content, curiosity about da'wah material, and readiness to convert partially and simultaneously have a positive and significant effect on the effectiveness of da'wah and social media.